Temperatture esttiimattiion off EXDRA and SSUMI dwarff Nova systtems from spectroscopic data - Kadhem, Arshed Ali (Iraqi Journal of Physics, 2019)
The seasonal behavior of the light curve for selected star SS UMI and EXDRA during outburst cycle is studied. This behavior describes maximum temperature of outburst in dwarf nova. The raw data has been mathematically modeled by fitting Gaussian function based on the full width of the half maximum and the maximum value of the Gaussian. The results of this modeling describe the value of temperature of the dwarf novae star system leading to identify the type of elements that each dwarf nova consisted of.